Step
*
2
1
of Lemma
qexp-minus-one
1. n : ℤ
2. 0 < n
3. -1 ↑ n - 1 = if (n - 1 rem 2 =z 0) then 1 else -1 fi  ∈ ℚ
⊢ (if (n - 1 rem 2 =z 0) then 1 else -1 fi  * (-1)) = if (n rem 2 =z 0) then 1 else -1 fi  ∈ ℚ
BY
{ xxxAssert ⌜(((n - 1 rem 2) = 0 ∈ ℤ) ∧ ((n rem 2) = 1 ∈ ℤ)) ∨ (((n - 1 rem 2) = 1 ∈ ℤ) ∧ ((n rem 2) = 0 ∈ ℤ))⌝⋅xxx }
1
.....assertion..... 
1. n : ℤ
2. 0 < n
3. -1 ↑ n - 1 = if (n - 1 rem 2 =z 0) then 1 else -1 fi  ∈ ℚ
⊢ (((n - 1 rem 2) = 0 ∈ ℤ) ∧ ((n rem 2) = 1 ∈ ℤ)) ∨ (((n - 1 rem 2) = 1 ∈ ℤ) ∧ ((n rem 2) = 0 ∈ ℤ))
2
1. n : ℤ
2. 0 < n
3. -1 ↑ n - 1 = if (n - 1 rem 2 =z 0) then 1 else -1 fi  ∈ ℚ
4. (((n - 1 rem 2) = 0 ∈ ℤ) ∧ ((n rem 2) = 1 ∈ ℤ)) ∨ (((n - 1 rem 2) = 1 ∈ ℤ) ∧ ((n rem 2) = 0 ∈ ℤ))
⊢ (if (n - 1 rem 2 =z 0) then 1 else -1 fi  * (-1)) = if (n rem 2 =z 0) then 1 else -1 fi  ∈ ℚ
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  0  <  n
3.  -1  \muparrow{}  n  -  1  =  if  (n  -  1  rem  2  =\msubz{}  0)  then  1  else  -1  fi 
\mvdash{}  (if  (n  -  1  rem  2  =\msubz{}  0)  then  1  else  -1  fi    *  (-1))  =  if  (n  rem  2  =\msubz{}  0)  then  1  else  -1  fi 
By
Latex:
xxxAssert  \mkleeneopen{}(((n  -  1  rem  2)  =  0)  \mwedge{}  ((n  rem  2)  =  1))  \mvee{}  (((n  -  1  rem  2)  =  1)  \mwedge{}  ((n  rem  2)  =  0))\mkleeneclose{}\mcdot{}xxx
Home
Index